The Implementation of SPEKS in Government Department : The Case of JKR Air, Kedah - Hamidah, Achmad (2005)
This study deals with the post implementation evaluation on SPEKS. SPEKS is an integrated accounting system package that been implemented in all Malaysian government sector since 2003. To accomplish this evaluation, 15 users from JKR Air Kedah were involved in the study. This study has tried to measure system success and identify the strength and weakness of the system. To measure system success, DeLone & McLean (1992) model of information system success was used. SPEKS strength and weakness was identified by using the usability questionnaire guideline. Suggestion to overcome each weakness and problems faced by SPEKS users is also given. The result shows that SPEKS implementation is a success, but a lot of modifications need to be done to improve its performance.